Analysis of Gottingen 428 Airfoil Turbine Propeller Design with Computational Fluid Dynamics Method on Gravitational Water Vortex Power Plant - Ede Mehta Wardhana; Agoes Santoso; Asep Rahmat Ramdani (Institut Teknologi Sepuluh Nopember, 2019)
Along with technological development and the increase in human population, the electricity needs are increasing every year. However, 94% of power plant in Indonesia still using fossil fuels that are pollutant and non-renewable. In addition, NASA said that the earth's temperature had risen by 1°C since 1880 and the current carbon dioxide level was the highest in the last 650,000 years. Therefore, Indonesia need to improve, in fact Indonesia is one of the highest emission contributors in the world. Indonesia is not yet 100% electrified, there are still 2,519 villages without electricity. Gravitational Water Vortex Power Plant (GWVPP) which is a micro hydro-power plant may answer the problem, because it is an easy renewable energy to be made and utilized in the NIZ (not interconnected zones) region. This study will examine the changes in the number and shape of the blade, as well as the length of the chord, to know the effect on turbine power so that it can produce higher efficiency at GWVPP. Propeller turbine with a Gottingen 428 airfoil analyzed using Computational Fluid Dynamics (CFD) method. The results show that the number of blades and the length of the chord is inversely proportional to the efficiency of the turbine, and the shape of blade is more efficient when it’s twisted.